Feedback and self‐regulated learning: insights from supervisors' and PhD examiners' reports - Stracke, Elke; Kumar, Vijay (Routledge, 2010)
This paper provides insights into the doctoral journey of a supervisee by analysing written feedback provided by supervisors and thesis examiners. As one aim of doctoral education is to train scholars to become independent researchers, that is highly self‐regulated learners, this study paves the way for an understanding of the link between written feedback and the self‐regulated learning process. Based on an analysis of speech functions, written feedback provided by two supervisors and three examiners were classified into three main categories: referential, directive and expressive. The results indicate the value of expressive feedback for the development of self‐regulated learning in doctoral supervision.